Technological Feasibility for the Application of Cellular Manufacturing in a Typical Costume Workshop (Caporales) - Maldonado Galvan, Carlos Joao (2023)
The objective of this article is to verify the technological feasibility of the installation of a workshop for the production of typical caporal costumes based on the Cellular Manufacturing methodology. By taking samples of times used in the production process, the standard times of each activity were obtained considering constant and variable supplements resulting from the different conditions to which the operators are exposed. It was determined that, under the chosen methodology, the process needs 6 operators and 8 machines to cover the projected demand of 897 suits per month, with a production capacity of 17.89 suits per day. Finally, a u-shaped distribution of the workshop was proposed, which maintains a constant flow within the process and allows exploiting the versatility of the workers